Food intake, gut transit time and defecation pattern of Asian horseshoe crab, Tachypleus gigas - Md Razak, Mohd Razali; Kassim, Zaleha (Akademi Sains Malaysia, 2018)
Nowadays, the numbers of wild horseshoe crab harvested for study are increasing. However, general information on Tachyplues gigas satiation level, gut transit time, defecation pattern and acclimation period in captivity during holding period are still scanty. The aims of this study are to identify T. gigas food intake, gut transit time and defecation pattern during the rearing period by introducing the crabs with gastropod (Turritella sp.), crustacean (Squilla sp.) and bivalve (Meretrix meretrix ) in several feed ratios; 0.2%, 0.6%, 1.0%, 1.4%, 1.8% and 2.2% expressed of crabs’ body weight. The defecation of T. gigas was monitored for every three hours after being fed to measure their gut transit time and defecation pattern. Male crabs did not significantly eat until two weeks in captivity, while the females started to eat in the early first week after being harvested from the wild. The satiation levels of the females (gastropod: 1.8%±0.04; crustacean: 1.7%±0.08; bivalve: 1.8%±0.06) were significantly higher than the males’ (gastropod: 1.7%±0.08; crustacean: 1.4%±0.02; bivalve: 1.6%±0.05) for all feed types. Gut transit time of the males were significantly longer than the females’. Male crabs took shorter time (1±0 hr) to achieve their satiation than female crabs (2±0 hrs). This study provides useful information for T. gigas rearing activity and for designing a better rearing system.